Analisis Pelaksanaan Manajemen Laboratorium Pada Pembelajaran Biologi Kelas XI SMA Negeri Kabupaten Muaro Jambi: Analysis of Implementation of Laboratory Management on Biology Learning Class XI SMA Negeri Muaro Jambi - Mariza Fiska; Afreni Hamidah; Retni Sulistiyoning Budiarti (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2021)
A laboratory is a special place to carry out scientific activities. To support biology learning activities, every high school should have a laboratory with good management. This study aims to analyze the implementation of biological laboratory management at SMA Negeri Muaro Jambi Regency in planning, organizing, administering, structuring and securing. We collected data through observations, questionnaires, interviews, and documentation, then analyzed the data descriptively. The order of the highest observation scores was from SMAN Titian Teras (3.67) in a very good category with a percentage of 91.75%, SMAN 1 (3.44) in a good category (86%), and SMAN 3 (2.88) in a bad category (72%). The results of scoring questionnaires and interviews on the implementation of laboratory management by biology teachers were the highest from SMAN Titian Teras (3.47) in a good category with a percentage of 86.75%, SMAN 1 (3.38) in a good category (84.5%) and SMAN 3 (3.08) not in a good category (77%). The scoring of the interview results from SMAN Titian Teras (3.76), a very good category with a percentage of 94%, SMAN 1 (3.76), a very good category with a percentage of 94%, and SMAN 3 (3.30), not a good category (82.5%). This study concludes that the implementation of laboratory management at SMA Negeri Muaro Jambi Regency is well implemented.